2008
DOI: 10.1242/jcs.021931
|View full text |Cite
|
Sign up to set email alerts
|

Haemocyte-derived SPARC is required for collagen-IV-dependent stability of basal laminae inDrosophilaembryos

Abstract: The authors wish to publish the following addendum to J. Cell Sci. 121, 1671-1680.Further characterization of the SPARC-null fly line Df(3R)nm136, generated by P-element mutagenesis, has revealed that the line carries a secondary mutation in the neuralized locus, in addition to an absence of SPARC. We have confirmed in a wild-type neuralized background that the absence of SPARC leads to a reduction of collagen IV in basal lamina in stage 17 mutant embryos. The absence of SPARC does not affect neural developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 79 publications
5
87
1
Order By: Relevance
“…Within a few months, cataracts become visible in Sparc-null mice, a deformity hypothesized to be attributed in part to decreased collagen IV stability in lens capsules (Greiling et al 2009;Norose et al 1998). SPARC is enriched in basal laminae of Drosophila melanogaster embryos, and in the absence of SPARC collagen IV, incorporation is de-regulated, consistent with the finding of compromised collagen maturation and/or stability in Sparc-null mice (Martinek et al 2008;Rentz et al 2007). In both Ceanorhabditis elegans and D. melanogaster, the absence of SPARC proves embryonic lethal (Fitzgerald and Schwarzbauer 1998;Martinek et al 2007;Schwarzbauer et al 1994;Schwarzbauer and Spencer 1993).…”
Section: Introductionsupporting
confidence: 80%
“…Within a few months, cataracts become visible in Sparc-null mice, a deformity hypothesized to be attributed in part to decreased collagen IV stability in lens capsules (Greiling et al 2009;Norose et al 1998). SPARC is enriched in basal laminae of Drosophila melanogaster embryos, and in the absence of SPARC collagen IV, incorporation is de-regulated, consistent with the finding of compromised collagen maturation and/or stability in Sparc-null mice (Martinek et al 2008;Rentz et al 2007). In both Ceanorhabditis elegans and D. melanogaster, the absence of SPARC proves embryonic lethal (Fitzgerald and Schwarzbauer 1998;Martinek et al 2007;Schwarzbauer et al 1994;Schwarzbauer and Spencer 1993).…”
Section: Introductionsupporting
confidence: 80%
“…Initially discovered as a bone matrix protein [65] osteonectin/SPARC has then been cloned as stress-response gene [66]. Accordingly, in vivo, SPARC can work as chaperon [67] particularly on collagen [68]. During collagen deposition, it works in concert with HSP47 to ensure that only correctly folded pro-collagen molecules exit the endoplasmic reticulum to promote collagen fibrillogenesis [69].…”
Section: Sparcmentioning
confidence: 99%
“…TRITC-conjugated phalloidine (Sigma) was used for F-actin detection. We used the following primary antibodies: sheep anti-digoxygenin (1:1,000, Boehringer), rabbit anti-dystroglycan Dg ex8 (1:500) [42], rat antiDrosophila-epithelial-cadherin (1:100, DSHB) [43], mouse anti-fasciclin II (1:10, DSHB) [44], mouse anti-fasciclin III (1:10) [45], rat anti-filamin1/cheerio (1:500) [46], rabbit anti-b-galactosidase (1:2,500, Cappel), rabbit anti-green fluorescent protein (1:500, abcam), rabbit anti-lamininB2 (1:300, abcam), rabbit anti-laminin (1:500) [47], mouse anti-macrophage-derived-proteoglycan-1 (1:200) [48], rabbit anti-nidogen (1:5,000) [28], mouse anti-pericardin EC11 (1:5, DSHB) [49], rabbit anti-serpent (1:500, gift from Rolf Reuter), rabbit anti-SPARC (1:500) [50] and guinea-pig anti-b3tubulin (1:6,000) [51]. We used Cy2 and Cy3-conjugated secondary antibodies at 1:100 (Dianova), pre-absorbed biotinylated secondary antibodies at 1:500 in combination with the Vectastain ABC Kit Standard (Vector Laboratories) and the TSA Amplification Renaissance Kits (PerkinElmer).…”
Section: Fly Stocks and Geneticsmentioning
confidence: 99%
“…4j-l), SPARC is still expressed in hemocytes and the fat body but secretion and extracellular deposition appears sparsely, indicating that SPARC deposition depends on laminin. Recent analysis of SPARC mutant embryos revealed that collagen IV deposition in the BM is impaired [50]. Therefore, we analyzed the distribution of a type IV collagen encoded by the viking (vkg) locus utilizing G454, a GFP protein trap allele of vkg (vkg G454 ).…”
Section: Laminin Expression and Localization During Embryogenesismentioning
confidence: 99%